Accuracy of MRI and Varus Stress Radiographs in Diagnosing Fibular Collateral Ligament Injuries. Issue 7 (30th July 2018) - Provencher, Matthew T.; Kane, Patrick W.; DePhillipo, Nicholas N.; Cinque, Mark; Moatshe, Gilbert; Murphy, Colin; Sanchez, Anthony; LaPrade, Robert F.
Objectives: To evaluate the diagnostic accuracy of magnetic resonance imaging and varus stress radiographs for FCL tears, and compare these modalities to intraoperative findings. Methods: All patients who underwent an isolated FCL or combined ACL/FCL reconstruction by a single surgeon between 2010 and 2017 with preoperative varus stress radiographs and MRI were included in this study. A control group was comprised of patients with an MRI and intact ACL and FCL. Sensitivity and specificity of diagnosing FCL injuries on MRI were determined based on review by a fellowship-trained musculoskeletal radiologist. The sensitivity of diagnosing an FCL injury based on varus stress radiographs was also determined. Furthermore, the ability of both imaging modalities to identify an FCL injury was stratified based on acute versus chronic etiology. Results: A total of 232 patients were included: 98 patients in the FCL tear group and 134 patients in the control group. Varus stress radiographs were determined to be more sensitive in diagnosing FCL injuries compared to MRI, with an overall sensitivity of 70% compared to 66%. Based on chronicity of the injuries, MRI was more accurate for detecting acute FCL injuries than chronic injuries (p=0.002), and varus stress radiographs were more accurate for detecting chronic FCL injuries than acute injuries (p=0.041). Conclusion: To our knowledge, this is the first clinical study to directly compare the diagnostic accuracy of FCL tear detection utilizing MRI and varus stress radiographs in the same patient cohort. While varus stress radiographs appear to have a higher accuracy overall, the results from our study support the use of both varus stress radiographs and MRI in diagnosing FCL injuries, as MRI is more sensitive in diagnosing an acute FCL tear, and varus stress radiographs are more sensitive in diagnosing a chronic FCL tear.